Preparation method of bergamolactone nanocrystals

The preparation of bergamot lactone nanocrystals by combining film hydration and micromedia grinding has solved the problem of low solubility in water and significantly improved the bioavailability and efficacy.

CN119606877APending Publication Date: 2025-03-14CHONGQING MEDICAL & PHARMA COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821620.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The extremely low solubility of bergamot lactone in water leads to its low bioavailability, limiting its application in pharmaceutical preparations.

Method used

Bergo lactone nanocrystals were prepared by combining film hydration and micro-media grinding. The organic solvent was removed by rotary evaporation under reduced pressure, and hydration and dispersion were performed to finally obtain a BER nanocrystal suspension.

Benefits of technology

It significantly improves the dissolution performance of bergamot lactone, improves its bioavailability, and enables the drug to be better absorbed and utilized by the body, thereby improving its pharmacological effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119606877A_ABST
    Figure CN119606877A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medicines, and discloses a preparation method of bergamolactone nanocrystals, which comprises the following steps: S1, weighing bergamolactone and a stabilizer according to a mass ratio of 5: (1-4), then adding a proper amount of an organic solvent for dissolving, and then removing the organic solvent by adopting a reduced pressure rotary evaporation process to obtain a medicine / stabilizer film; s2, performing hydration treatment on the drug / stabilizer film obtained in the S1 to obtain a drug solution; s3, after hydration is completed, the medicine solution in the S2 is subjected to dispersion treatment, and a medicine suspension is prepared; and S4, adding the medicine suspension prepared in the S3 into a medium grinding chamber, and carrying out grinding treatment to obtain a BER nanocrystalline suspension, namely BER-NCs. According to the technical scheme, the problems of low solubility and poor bioavailability of bergamolactone in water can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medicines, and in particular to a method for preparing bergamot lactone nanocrystals. Background Art

[0002] Bergapten (BER) belongs to the psoralen class of compounds and is widely found in bergamot and other citrus essential oils. As a natural drug monomer, BER has a stable chemical structure and possesses a variety of pharmacological and biological activities. It has shown significant efficacy in antibacterial, anti-inflammatory, anti-cancer, immunomodulatory, and inducing cell apoptosis, and has been successfully used as a photosensitizer in the medical field. For example, in traditional treatment methods, psoralen is often used in combination with ultraviolet-A (UVA) for the clinical treatment of skin diseases such as psoriasis, vitiligo, and eczema, and has achieved certain therapeutic effects. At the same time, relevant studies have shown that the interaction between BER and UVA can effectively induce the melanin synthesis process of mouse melanoma cells and normal human melanocytes, and this melanin production phenomenon may be closely related to the upregulation of intracellular tyrosinase expression levels.

[0003] Although bergamot lactone has broad application prospects in terms of pharmacological activity, it faces a very severe challenge in the development and application of pharmaceutical preparations, namely, its extremely low solubility in water. This low solubility property greatly limits the bioavailability of BER, making it difficult to achieve ideal drug absorption effects whether it is administered orally or transdermally. This not only seriously hinders BER from exerting its due pharmacological effects in vivo, but also causes significant delays and obstacles to the development of new drugs based on bergamot lactone.

[0004] In view of the above situation, in the field of modern pharmacy and the pharmaceutical industry, developing innovative bergamot lactone delivery systems, focusing on improving the solubility of bergamot lactone in water, and effectively solving the problem of its low bioavailability has become a research hotspot and a key technical problem that needs to be overcome by relevant professional scientific researchers and pharmaceutical R&D workers. By solving this key problem, it is expected to further expand the application scope of bergamot lactone in the pharmaceutical field, provide more effective drug treatment methods for the treatment of various diseases, and promote the innovative development and progress of the pharmaceutical industry. Summary of the invention

[0005] The present invention aims to provide a method for preparing bergamot lactone nanocrystals to solve the problems of low solubility and poor bioavailability of bergamot lactone in water.

[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing bergamot lactone nanocrystals, comprising the following steps:

[0007] S1: weighing bergamot lactone and stabilizer in a mass ratio of 5:(1-4), then adding an appropriate amount of organic solvent to dissolve, and then removing the organic solvent by a reduced pressure rotary evaporation process to obtain a drug / stabilizer film;

[0008] S2: hydrating the drug / stabilizer film obtained in S1 to obtain a drug solution;

[0009] S3: After the hydration is complete, the drug solution in S2 is dispersed to obtain a drug suspension;

[0010] S4: Add the drug suspension prepared in S3 into the medium grinding chamber for grinding to obtain BER nanocrystal suspension, i.e., BER-NCs.

[0011] Preferably, in S1, the stabilizer is polyoxyethylene sorbitan monooleate.

[0012] Preferably, in S2, the hydration process is: add an appropriate amount of deionized water to the drug / stabilizer film obtained in S1 to prepare a drug solution, transfer it to a constant temperature magnetic stirrer, and hydrate it at room temperature for 5-6 hours.

[0013] Preferably, in S2, the concentration of the drug solution is 5 mg / mL.

[0014] Preferably, in S3, the dispersion treatment process is: in an ice water bath environment, an ultrasonic cell pulverizer is used to disperse the drug solution in S2, the power of the ultrasonic cell pulverizer is 600W, the dispersion time is 15min, and it is turned on for 1s and stopped for 1s.

[0015] Preferably, in S4, the grinding media are zirconium oxide beads.

[0016] Preferably, in S4, the volume ratio of grinding media to drug suspension is (1.8-2.2):1.

[0017] Preferably, in S4, the diameter of the zirconium oxide beads is 0.15-0.2 mm.

[0018] Preferably, in S4, the grinding speed is 950-1100 rpm.

[0019] Preferably, in S4, the grinding time is 12-16 hours.

[0020] The beneficial effects of this program are:

[0021] (1) Particle size and morphology advantages: Bergamot lactone nanocrystals with an average particle size of (215.9±2.9) nm, an average polydispersity coefficient of 0.226±0.008, and a Zeta potential of (-16.80±0.27) mV were successfully prepared. They are in the shape of small and short rods with relatively uniform size. This specific particle size and morphology facilitates the distribution and action of the drug in the body.

[0022] (2) Stable crystal form and chemical structure: Various analytical methods (DSC, XRPD, FTIR) confirmed that the crystal form and chemical structure of bergamot lactone did not change significantly before and after nano-enzyme processing, ensuring that the original properties and activity of the drug were retained and reducing the impact on drug quality that may be caused by changes in crystal form.

[0023] (3) Improved dissolution performance: The BER-NCs drug solubility prepared by this technical solution is significantly improved, which effectively solves the problem of low bioavailability of bergamot lactone due to its poor solubility, allowing the drug to be better absorbed and utilized by the body, thereby improving its pharmacological effect and providing a more effective drug treatment for the treatment of various diseases.

[0024] (4) Preparation process advantages: The preparation method combining thin film hydration and micro-media grinding is feasible and has unique advantages. On the one hand, this method can effectively prepare nano-preparations, and the preparations only contain drugs and stabilizers, without introducing organic solvents and other impurities, thereby improving the purity and safety of the preparations; on the other hand, the high drug loading is more conducive to industrial production, reducing production costs and improving production efficiency, providing a reliable process basis for the large-scale preparation of bergamot lactone nanocrystal preparations, and has broad application prospects and economic value in the pharmaceutical industry.

[0025] (5) The stabilizer has a significant effect: It is determined that when Tween 80 is used as a stabilizer, bergamot lactone nanocrystals with smaller particle sizes can be prepared. It can form a mechanical and thermodynamic barrier at the interface, reduce the surface tension between the nanocrystals and the medium solution, and further optimize the preparation effect and quality of the nanocrystals.

[0026] (6) High process reliability: In the process of optimizing the preparation process by Box-Behnken response surface methodology, the lack of fit term was not significant, the model had good fit and high predictability, and there was no significant difference between the measured values ​​and the predicted values ​​of the samples prepared in the verification test, and the relative deviation was small, indicating that the established preparation process was reasonable and reliable, providing a stable and repeatable process guarantee for subsequent experiments and industrial production, reducing process errors and batch differences, and helping to ensure the consistency and stability of product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A is the investigation result of the mass ratio of the drug to the stabilizer in Experimental Example 1 of the present invention;

[0028] Figure 1 B is the investigation result of hydration time in Experimental Example 1 of the present invention;

[0029] Figure 1 C is the investigation result of the amount of grinding media used in Experimental Example 1 of the present invention;

[0030] Figure 1 D is the investigation result of the grinding medium diameter in Experimental Example 1 of the present invention;

[0031] Figure 1 E is the investigation result of the ultrasonic cell pulverizer power and ultrasonic time in Experimental Example 1 of the present invention;

[0032] Figure 1 F is the investigation result of the medium grinding time in Experimental Example 1 of the present invention;

[0033] Figure 2 The scanning electron microscope images of the BER API in Experimental Example 3 of the present invention and the BER-NCs prepared according to the preparation process of Example 1;

[0034] Figure 3 FTIR images of the BER API, the physical mixture of the BER API and the stabilizer Tween-80, and the BER-NCs in Experimental Example 3 of the present invention;

[0035] Figure 4 The DSC graphs of the BER API, the physical mixture of the BER API and the stabilizer Tween-80, and the BER-NCs in Experimental Example 3 of the present invention;

[0036] Figure 5 The XRPD patterns of the BER API, the physical mixture of the BER API and the stabilizer Tween-80, and the BER-NCs in Experimental Example 3 of the present invention;

[0037] Figure 6 It is a HPLC specificity graph of the reference solution, the test solution and the negative solution in Experimental Example 3 of the present invention;

[0038] Figure 7 The chromatogram of the BER reference substance in Experimental Example 3 of the present invention;

[0039] Figure 8 1 is the in vitro release curve of the BER API in Experimental Example 3 of the present invention and the BER-NCs prepared according to the preparation process of Example 1 (x±s, n=3). DETAILED DESCRIPTION

[0040] The following is further described in detail through specific implementation methods:

[0041] Example 1

[0042] Main instruments

[0043] Zeta potential-laser particle size analyzer (Malvern Instruments Ltd., UK, model: ZEN3600); ultrasonic cell pulverizer (Ningbo Xinzhi Biotechnology Co., Ltd., model: SCIENTZ-IID); scanning electron microscope (Phenom World, model: Phenom PRO); high performance liquid chromatograph (Thermo-fisher, USA, model: Ultimate3000); differential scanning calorimeter (NETZSCH, Germany, model: 200pc); X-ray diffractometer (Dandong Tongda Technology Co., Ltd., model: TD3500); electronic balance (Shanghai Precision Instrument Technology Co., Ltd., model: YP6000N); Fourier transform infrared scanner (PerkinElmer Co., Ltd.; model: Spectrum Two); SHA-BA water bath constant temperature oscillator.

[0044] Main reagents

[0045] BER API (purity ≥ 98%, Shanghai Bidex Pharmaceutical Co., Ltd., batch number: CPZ894); BER reference substance (purity ≥ 98%, Chongqing Meisai Biotechnology Co., Ltd., batch number: 221009), Tween 80 (Shanghai McLean Biochemical Technology Co., Ltd., batch number: 069811002100); dichloromethane (Shanghai McLean Biochemical Technology Co., Ltd., batch number: C15378100); sodium dodecyl sulfate (SDS, Beijing Solebao Technology Co., Ltd., batch number: 1019Y031); PBS phosphate buffer (pH 7.4, Shanghai Yuanye Biotechnology Co., Ltd., batch number: O30IR19280A); dialysis bag (Beijing Solebao Technology Co., Ltd., molecular weight cutoff 8000-14000D, batch number: 24230816004); laboratory water is ultrapure water.

[0046] A method for preparing bergamot lactone nanocrystals comprises the following steps:

[0047] S1: Weigh bergamot lactone (BER API) and stabilizer in a mass ratio of 5:(1-4) and place them in a round-bottom flask. Then, add an appropriate amount of organic solvent into the flask and shake it thoroughly to dissolve it. Then, remove the organic solvent by a reduced pressure rotary evaporation process to obtain a drug / stabilizer film;

[0048] In this step, the mass ratio of bergamot lactone to the stabilizer is 5:1; the stabilizer is polyoxyethylene sorbitan monooleate (Tween 80); the organic solvent is dichloromethane; the reduced pressure rotary evaporation process is implemented using a rotary evaporator. Specifically, in this embodiment, the mass of bergamot lactone is 0.1 g, the mass of Tween 80 is 0.02 g, and the volume of dichloromethane is 5 mL;

[0049] S2: hydrating the drug / stabilizer film obtained in S1 at room temperature for 5-6 hours to obtain a drug solution;

[0050] In this step, 20 mL of deionized water was added to the drug / stabilizer film obtained in S1 to prepare a drug solution with a concentration of 5 mg / mL. The solution was transferred to a constant temperature magnetic stirrer and hydrated at room temperature for 5 h before being taken out.

[0051] S3: After the hydration is complete, the drug solution in S2 is dispersed to obtain a drug suspension;

[0052] In this step, the dispersion process is as follows: in an ice-water bath environment, an ultrasonic cell pulverizer is used to disperse the drug solution in S2. The power of the ultrasonic cell pulverizer is 600W, the dispersion time is 15min, it is turned on for 1s and stopped for 1s, and an intermittent operation mode of turning on for 1s and stopping for 1s is adopted. The purpose is to effectively prevent the sample from being overheated due to long-term heating, thereby avoiding damage to the sample. Because if the operation is carried out continuously for a long time, it will inevitably lead to excessive heat accumulation. At the same time, the instrument will be easily damaged due to being in a high-load operation state for a long time, which will have an adverse effect on the service life of the instrument;

[0053] S4: adding the drug suspension prepared in S3 into the medium grinding chamber for grinding to obtain BER nanocrystal suspension, i.e., BER-NCs;

[0054] In this step, a magnetic stirrer is used as a power device, a cillin bottle is used as a grinding chamber, and zirconium oxide beads are used as grinding media. The drug suspension prepared in S3 is added to the medium grinding chamber, and zirconium oxide beads with a diameter of 0.15-0.2 mm are added according to a volume ratio of grinding media to drug suspension of (1.8-2.2):1, and the grinding speed is set to 950-1100 rpm, and the grinding is performed for 12-16 hours to obtain BER-NCs. In this embodiment, the volume ratio of grinding media to drug suspension is 2:1, the diameter of zirconium oxide beads is 0.2 mm, the grinding speed is 1000 rpm, and the grinding is performed for 12 hours.

[0055] This technical solution uses a combination of thin film hydration and micro-media grinding to prepare bergamot lactone nanocrystals (BER-NCs). The prepared BER-NCs present a small and short rod-like morphology, with a relatively uniform size, an average particle size of (215.9±2.9)nm, an average polydispersity index (PDI) of 0.226±0.008, and a Zeta potential value of (-16.80±0.27)mV. It has been verified by a variety of detection methods that the crystal form and chemical structure of bergamot lactone did not change significantly before and after nano-sizing. More importantly, after the nanocrystals were made, the solubility of the drug was significantly improved. Based on the above results, it can be seen that the preparation method combining thin film hydration and micro-media grinding is feasible. The prepared nanocrystals not only have a uniform size distribution, but also can effectively improve the original dissolution performance of bergamot lactone, providing strong support for its further application in the field of pharmaceutical preparations.

[0056] Experimental Example 1: Single Factor Investigation

[0057] (1) Screening of stabilizer types

[0058] Generally speaking, the type of stabilizer used varies according to the specific properties of the drug, and is a prerequisite for affecting the particle size and distribution of drug nanoparticles. Therefore, the type of stabilizer is screened first.

[0059] In this experiment, PVP K90 (Shanghai Yuanye Biotechnology Co., Ltd., batch number: S23HS195870), F68 (Beijing Solebow Technology Co., Ltd., batch number: 1229P021), CMC-Na (Shanghai Titan Technology Co., Ltd., batch number: P2694091), SDS, and Tween 80 were used as stabilizers. BER-NCs were prepared using the preparation process of Example 1, and the particle size and average polydispersity index (PDI) of BER-NCs were calculated. The results are shown in Table 1.

[0060] From the data in Table 1, it can be seen that when CMC-Na and SDS were used as stabilizers for preparation, the particle size did not reach the nanoscale and aggregation and adsorption occurred. That is, in the process of preparing NCs, due to the increase in surface area, a thermodynamically unstable system was formed, and the crystals aggregated and adsorbed to reduce the free energy of the system, which was directly manifested as an increase in particle size. Although the particle sizes of PVP K90 and F68 reached the nanoscale, the PDI was greater than 0.3. In the preparation of nanocrystalline drugs, PDI less than 0.3 is usually considered to be an ideal state, because it indicates that the particle size distribution is very uniform, which helps to improve the stability and bioavailability of the drug. When the stabilizer is Tween80, the particle size can reach the nanoscale, and the PDI is less than 0.3, indicating that Tween 80 is used as a stabilizer to obtain a BER-NCs suspension with a small and uniform particle size.

[0061] Table 1

[0062] Experimental groups Stabilizer Type Particle size (nm) PDI Experimental Group 1 SDS 1110.0±92.1 0.474±0.098 Experimental Group 2 PVP K90 335.6±9.0 0.446±0.042 Experimental Group 3 Tween 80 229.7±4.5 0.241±0.015 Experimental Group 4 CMC-Na 1471.1±87.7 0.313±0.114 Experimental Group 5 F68 244.9±14.3 0.337±0.043

[0063] (2) Investigation of the mass ratio of drug (bergamot lactone) to stabilizer

[0064] In this experiment, Tween 80 was used as a stabilizer, the mass ratio of BER to Tween 80 was used as a variable, and the other parameters were kept the same as in Example 1. The effects of the mass ratio of BER to Tween 80 of 5:1, 5:2, 5:3, and 5:4 on the particle size and average polydispersity index (PDI) of BER-NCs were investigated. The results are shown in FIG. Figure 1 As shown in A.

[0065] like Figure 1 As shown in Figure A, when the mass ratio of BER to Tween 80 is 5:1, 5:2, 5:3, and 5:4, the differences in the influence of the particle size and average polydispersity index (PDI) of the formed BER-NCs are not obvious. When the mass ratio of BER to Tween 80 is further reduced, when the mass ratio of BER to Tween 80 is 5:0.5, it is difficult to completely form the initial nanocrystals. When the mass ratio of BER to Tween80 is 5:1, the theoretical content of BER is 83.33%, which is higher than the nanocrystals prepared at other ratios. Therefore, considering the above factors, the mass ratio of BER to Tween 80 is 5:1 to prepare nanocrystals.

[0066] (3) Investigation of hydration time

[0067] In this experiment, Tween 80 was used as a stabilizer, hydration time was used as a variable, and the other parameters were kept the same as those in Example 1. The effects of hydration time of 0.5, 1.0, 1.5, 2.0, 3.0, 4.0, and 5.0 h on the particle size and average polydispersity index (PDI) of BER-NCs were investigated. The results are shown in Table 1. Figure 1 As shown in B.

[0068] like Figure 1 As shown in B, the longer the hydration stirring time, the more uniform the particle size distribution. After 5.0 h, a uniform nanocrystal solution can be basically obtained, so 5.0 h is selected as the hydration time for preparing BER-NCs.

[0069] (4) Investigation of ultrasonic cell pulverizer power and ultrasonic time

[0070] In this experiment, Tween 80 was used as a stabilizer, and the power and time of the ultrasonic cell pulverizer were used as variables. The other parameters were kept the same as those in Example 1. The effects of the power and time of the ultrasonic cell pulverizer at 500w for 15min, 500w for 5min, then 600w for 10min, and 600w for 15min on the particle size and average polydispersity index (PDI) of BER-NCs were investigated. The results are shown in Table 1. Figure 1 As shown in C.

[0071] like Figure 1 As shown in Figure C, with the increase of ultrasonic cell crusher power and the extension of ultrasonic time, the particle size of BER-NCs decreased and the dispersibility was improved. In order to obtain Ber-NCs with moderate particle size and good dispersion, the probe ultrasonic time was finally selected to be 15 min and the probe ultrasonic power was 600 w to prepare BER-NCs.

[0072] (5) Investigation of grinding media diameter

[0073] In this experiment, Tween 80 was used as a stabilizer, the grinding medium diameter was used as a variable, and the other parameters were kept the same as in Example 1. The effects of grinding medium diameters of 0.2 mm and 0.4-0.6 mm on the particle size and average polydispersity index (PDI) of BER-NCs were investigated. The results are shown in Figure 1 As shown in D.

[0074] like Figure 1 As shown in Figure D, as the diameter of the zirconia beads decreases, the particle size of BER-NCs also decreases. Therefore, zirconia beads with a diameter of 0.2 mm were selected as the grinding media.

[0075] (6) Investigation of grinding media dosage

[0076] In this experiment, Tween 80 was used as a stabilizer, the amount of grinding media was used as a variable, and the other parameters were kept the same as in Example 1. The effects of the volume ratio of zirconium oxide beads to drug suspension of 0.5:1, 1:1, 1.5:1, 2:1, and 2.5:1 on the particle size and average polydispersity index (PDI) of BER-NCs were investigated. The results are shown in Table 1. Figure 1 As shown in E.

[0077] like Figure 1 As shown in Figure E, within the investigated ratio range, the particle size and average polydispersity index (PDI) of BER-NCs first decrease and then increase with the increase of the amount of zirconia beads. Considering the particle size and average polydispersity index (PDI), the volume ratio of zirconia beads to drug suspension was selected as 2:1.

[0078] (7) Investigation of medium grinding time

[0079] In this experiment, Tween 80 was used as a stabilizer, the medium grinding time was used as a variable, and the other parameters were kept the same as in Example 1. The effects of grinding time of 2h, 4h, 6h, 8h, 10h, 12h, 14h, and 16h on the particle size and average polydispersity index (PDI) of BER-NCs were investigated. The results are shown in Figure 1 As shown in F.

[0080] like Figure 1 As shown in Figure F, with the gradual extension of grinding time, the particle size and average polydispersity index (PDI) first decreased and then leveled off. In order to save experimental equipment consumption, the experimental grinding time was selected to be 12 h.

[0081] Experimental Example 2: Optimization of preparation process using Box-Behnken response surface methodology

[0082] Based on the single factor investigation results of Experimental Example 1, in order to further optimize the preparation process, the Box-Behnken response surface method was adopted. With particle size (Y1) and average polydispersity coefficient (Y2) as response values, three factors with greater influence, namely hydration time (X1), volume ratio of grinding medium to drug suspension (X2), and grinding time (X3), were selected to optimize the preparation process. DesignExpert13 software was used to perform a 3-factor 3-level experimental design. Table 2 is the factor level table, Table 3 is the experimental design and results, and Table 4 is the results of variance analysis.

[0083] Table 2

[0084]

[0085] Table 3

[0086]

[0087]

[0088] Table 4

[0089]

[0090]

[0091] Model fitting and result analysis: Design Expert13 software was used for multiple linear regression, and the linear regression equations of the particle size Y1 and average polydispersity coefficient Y2 of BER-NCs were obtained as follows:

[0092] Y1=367.86-31.05X1-110.89X2-28.44X3-72.75X1X2+19.75X1X3-17.63X2X3+42.98X1 2 +46.56X2 2

[0093] -25.69X3 2 (The model's coefficient of determination R 2 =0.9829, Corrected determination coefficient R 2 =0.9609, P<0.0001);

[0094] Y2=0.28-0.020X1-0.016X2-0.070X3-1.500×10 -3 X1X2+0.035X1X3-0.021X2X3+2.675×10 -3 X1 2 -

[0095] 3.075×10 -3 X2 2 +0.050X3 2 (The model's coefficient of determination R 2 =0.9803, Corrected determination coefficient R 2 =0.9551, P<0.0001);

[0096] From the analysis of variance table 4, it can be seen that the prediction model is extremely significant (P<0.01), among which X1, X2, X3, X1X2, X1 2 , X2 2 There were significant differences (P<0.01), X3 2 There is a significant difference (P<0.05). The analysis shows that the order of factors affecting Y1 is X2>X1>X3; X1, X3, X1X3, X3 in equation Y2 2 There are significant differences (P<0.01), X2, X2X3 have significant differences (P<0.05), and the analysis shows that the order of Y2 affected by various factors is X1>X2>X3, indicating that the model can use this regression prediction model to optimize the preparation process conditions of bergamot lactone nanocrystals, and the model has a high degree of fitting, small experimental error conditions, and is highly scientific and statistical.

[0097] Verification experiment: Through the analysis of Design Expert13 software, the optimal preparation process conditions of bergamot nanocrystals are hydration time of 4.34h, grinding medium and drug suspension volume ratio of 2:1, grinding time of 11.85h, model predicted particle size value of 215.3nm, polydispersity coefficient of 0.225, three batches of samples were prepared in parallel according to the prescription, and the average of the three test data was taken, and the average particle size was measured to be 215.9nm, and the average polydispersity coefficient was 0.226. The results show that the response surface model is in good agreement with the actual situation and can effectively guide the optimization of the preparation process.

[0098] Experimental Example 3 Quality Characterization

[0099] (1) Morphological characterization of BER-NCs

[0100] First, BER raw material and BER-NCs prepared according to Example 1 were taken respectively, and they were uniformly adhered to the surface of the conductive adhesive, and then subjected to gold spraying. After the gold spraying, the sample was dried under a vacuum environment, and the drying temperature was set to 25°C and the drying time was 6 hours. After the drying was completed, the sample was placed under a scanning electron microscope to observe and record the surface morphology characteristics of the particles. The surface morphology of the BER raw material and the prepared BER-NCs is shown in FIG. Figure 2 shown.

[0101] like Figure 2 It can be seen that the surface morphology of the BER original drug is rectangular block-shaped crystals with uneven distribution; after being treated by the preparation process of Example 1, the particle size of the prepared BER-NCs is significantly reduced and the appearance is rounded. This morphological change gives it a larger surface energy, thereby bringing good expected effects for improving the solubility and dissolution rate of the drug in water, which is beneficial to improving the bioavailability and efficacy of the drug.

[0102] (2) Determination of average particle size, PDI and Zeta potential of BER-NCs

[0103] 1 mL of BER-NCs prepared according to the method of Example 1 was measured, and 10 mL of deionized water was added thereto. After being uniformly dispersed, the BER-NCs were measured by dynamic light scattering in a Zeta potential-laser particle size analyzer, and three sets of parallel samples were measured. The results obtained showed that the average particle size of BER-NCs reached 215.9 nm, the average polydispersity index (PDI) was 0.226±0.44, and the Zeta potential value was between (-16.8±0.270) mV, indicating that the particle size was relatively small and showed a relatively uniform distribution state in the system.

[0104] (3) FTIR chemical structure analysis

[0105] In order to further explore the changes in the chemical structure of BER in the process of preparing BER into BER-NCs according to the preparation process of Example 1, Fourier transform infrared spectroscopy (FTIR) was used to analyze its chemical structure, and a physical mixture (PM) prepared by mixing BER API and stabilizer Tween-80 in the same mass ratio as in Example 1 and BER API were selected as controls. The scanning range was set to 4000-400 cm -1 , resolution 4cm -1 .

[0106] Depend on Figure 3It can be seen that in BER API, the -1 The absorption peak in the interval is attributed to the stretching vibration of unsaturated CH, 2960cm -1 The absorption peak at 1720 cm -1 The absorption peaks at 1625 and 1605 cm are the stretching vibrations of ester C=O. -1 The absorption peaks at 1578, 1544, 1468, and 1357 cm-1 are derived from the stretching vibration of olefin C=C. -1 The absorption peaks at 1468 and 1382 cm are due to the skeleton vibration of the aromatic ring. -1 The absorption peaks at 1295 cm-1 are the antisymmetric and symmetric vibrations of the methyl group. -1 The absorption peaks at 603 and 500 cm are =CH in-plane bending vibrations. -1 The absorption peak at is the skeleton vibration of disubstituted olefin C=C.

[0107] In the physical mixture of BER API and stabilizer Tween-80 and BER-NCs, some new absorption peaks appeared, 3415 cm -1 The absorption peaks at 2923 and 2855 cm are the stretching vibrations of hydroxyl groups. -1 The absorption peaks at 1468 cm-1 are the antisymmetric and symmetric stretching vibrations of methylene. -1 The absorption peak at also represents the variable angle vibration of the methylene group, while the positions of other absorption peaks have not changed. This is because some functional groups (esters, ethers, and olefins) in Tween-80 are the same as bergamot lactone, which increases the absorption peak intensity of these groups. In summary, in the process of preparing BER into NCs, its chemical structure and composition have not changed significantly.

[0108] (4)DSC analysis

[0109] The crystal structure of BER-NCs prepared according to the preparation process of Example 1 was analyzed using a DSC analyzer. 10 mg of BER API, 10 mg of a physical mixture (PM) of BER API and stabilizer Tween-80 mixed in the same mass ratio as in Example 1, and 10 mg of BER-NCs prepared according to the preparation process of Example 1 were weighed using an electronic balance and added to a crucible respectively. Afterwards, a pinhole was pierced on the crucible cover, and then the cover was sealed. Under nitrogen protection, the heating rate was set to 20°C / min, and the test analysis was performed in the temperature range of 30-300°C.

[0110] Depend on Figure 4It can be seen that the BER raw material has a sharp endothermic peak at 192.85°C, while the melting points of the physical mixture and BER-NCs prepared by the preparation process of Example 1 have changed slightly, which are 191.37°C and 190.89°C, respectively, and the endothermic peak of BER-NCs is characterized by a wide peak and weak intensity.

[0111] (5) XRPD analysis

[0112] First, 50 mg of BER API, a physical mixture (PM) prepared by mixing BER API and stabilizer Tween-80 in the same mass ratio as in Example 1, and BER-NCs prepared according to the preparation process of Example 1 were taken. Subsequently, the sample was compacted using a glass slide, and the surrounding of the sample tank was wiped clean with an alcohol cotton ball. Then, the processed sample was placed in an XRPD analysis instrument for XRPD analysis, and the scanning speed of the sample was set to 5° / min, and the scanning range was continuously scanned from 5° (2θ) to 90° (2θ).

[0113] Depend on Figure 5 It can be seen that the BER API has characteristic diffraction peaks at 2θ of 12.02°, 13.15°, 18.83°, and 26.45°, indicating that the BER API exists in a crystalline state. In the XRPD spectrum of the physical mixture, the characteristic peaks of BER are basically retained, but after the nanosuspension is prepared by the preparation process of Example 1, the characteristic peaks are weakened and present a diffuse state, which indicates that in the process of preparing the nanosuspension, the crystal structure of the sample has undergone certain changes.

[0114] (6) Determination of content

[0115] a. Chromatographic conditions

[0116] The chromatographic column was Welch Ultimate XB-18 (250 mm × 4.6 mm × 5 μm); the detection wavelength was 320 nm; the detection column temperature was 30°C; the mobile phase was acetonitrile-0.1% acetic acid aqueous solution (volume ratio of 49:51); the injection volume was 10 μL, and the flow rate was 1.0 mL / min.

[0117] b. Solution preparation

[0118] Preparation of reference solution: Accurately weigh 6.18 mg of BER reference substance dried to constant weight, then add 50 mL of methanol to the weighed BER reference substance to completely dissolve it, and finally prepare a reference substance stock solution with a mass concentration of 123.6 μg / mL.

[0119] Preparation of the test solution: First, 200 μL of BER-NCs prepared according to the preparation process of Example 1 was measured and the volume was made up to 10 mL with methanol. After the volume was made up, the solution was first shaken thoroughly and then placed in an ultrasonic instrument with a power of 400 W for 10 min to achieve sufficient mixing to finally obtain the test solution.

[0120] Preparation of negative solution: First, accurately weigh the excipients according to the amount specified in the prescription. The excipients here specifically refer to all components other than the BER raw material in Example 1. Then, the same method as the preparation of the test solution is used, that is, weigh 200 μL of nanocrystals lacking bergamot lactone, place it in a volumetric flask, dilute it to 10 mL with methanol, then shake it well, and finally place the solution in an ultrasonic instrument for ultrasonic treatment. Through such a series of steps, a negative solution is finally obtained.

[0121] c. Exclusiveness inspection

[0122] Take the reference solution, the test solution and the negative solution respectively, place them in the HPLC injector, then start the HPLC according to the established chromatographic conditions in a, analyze and detect the above three solutions in turn, and record the chromatograms. Figure 6 It can be seen that BER-NCs showed a chromatographic peak at the same retention time as the BER reference, and the negative solution did not show a chromatographic peak, indicating that the excipients did not interfere with the determination of bergamot lactones under this detection condition.

[0123] d. Linear range

[0124] Accurately measure the BER reference substance, and use the two-fold dilution method to prepare a series of standard solutions with concentrations of 20.60μg / mL, 41.20μg / mL, 61.80μg / mL, 82.40μg / mL, and 123.60μg / mL. Filter through a 0.22μm microporous filter membrane, and use a high performance liquid chromatograph for sample analysis and determination. Record the chromatogram, see Figure 7 , with BER peak area (A) as ordinate and bergamot lactone standard solution concentration (C) as abscissa, linear regression was performed with A against C to draw a standard curve. The linear equation was obtained: Y = 0.6766X-2.8996, r = 0.9997. This shows that the peak area and concentration of bergamot lactone have a good linear relationship in the concentration range of 20.60-123.60 μg / mL.

[0125] e. Precision inspection

[0126] Pipette an appropriate amount of BER reference solution with a mass concentration of 123.60 μg / mL and place it in the HPLC injector. Then start the HPLC according to the established chromatographic conditions in a, measure 6 times in parallel, record the peak area, and calculate the precision. As a result, the RSD of the peak area of ​​the BER reference is 0.73% (n=6), indicating that the instrument precision is good and meets the methodological requirements.

[0127] f. Stability test

[0128] The same test solution was prepared and placed at room temperature for 0, 2, 4, 6, 8, 12, and 24 hours, respectively, and placed in the HPLC injector, and then the HPLC was started according to the established chromatographic conditions in a for determination, and the peak area was recorded. The RSD value of the peak area measured under this chromatographic method was 0.56%, indicating that the BER content was stable at room temperature for 24 hours.

[0129] g. Repeatability test

[0130] Take the BER-NCs prepared by the preparation process of Example 1 under the same batch, prepare 6 sample solutions in parallel, place them in the high performance liquid chromatograph injector, then start the high performance liquid chromatograph for determination according to the established chromatographic conditions in a, record the peak area, and calculate the content by the external standard method. The average concentration of bergamot lactone is 97.51 μg / mL, and the RSD value is 1.10%, which can indicate that the method has good repeatability.

[0131] h. Investigation of sample recovery rate

[0132] Accurately measure 2 mL of each of 9 portions of the same test solution with the determined content, and add BER reference substance, the ratio of the amount of BER reference substance added to the BER raw material in the test solution is 0.5:1, 1:1, 2:1, 3 portions for each ratio, dilute to 10 mL volumetric flask with methanol, mix well, and filter through a 0.22 μm microporous filter membrane. Place it in the injector of the high performance liquid chromatograph, and then start the high performance liquid chromatograph for determination according to the established chromatographic conditions in a, record the peak area of ​​bergamot lactone and calculate the recovery rate of the sample, the results are shown in Table 5.

[0133] As shown in Table 5, the recovery rate is between 98.43% and 101.06%, and the RSD is 0.93%, indicating that the recovery rate of this method is good.

[0134] Table 5

[0135]

[0136] (7) In vitro release study

[0137] The in vitro dissolution rate was determined by dialysis. The dialysis bag was activated, and PBS phosphate buffer solution (pH 7.4) containing 1% (w / v) SDS was selected as the dissolution medium. 5 mg of BER API and BER-NCs prepared according to the preparation process of Example 1 were weighed and added to the dialysis bag, and 1 mL of dissolution medium was added. The dialysis bag was placed in the dissolution bottle, and 100 mL of medium was added to the bottle. Three parallel experiments were performed. The bottle was oscillated horizontally at 100 r / min in a constant temperature oscillator at 37±0.5°C. 2 mL of samples were taken at 5 min, 10 min, 20 min, 40 min, 1 h, 2 h, 4 h, 6 h, 8 h, 12 h, and 24 h. At the same time, the release medium of the same temperature and volume was added. The sampled solution was filtered with a 0.45 μm microporous filter membrane, and the filtrate was taken and placed in the HPLC injector. Then, the HPLC was started according to the established chromatographic conditions in a for determination. The peak area was recorded to detect the bergamot lactone content, the dissolution amount was calculated, and the drug release-time curve was drawn. The cumulative release percentage (Q) at each time point was calculated as follows:

[0138]

[0139] Where C t is the drug concentration (mg / mL) in the release medium measured at each time point, W is the total weight of the drug input (mg), V0 is the total volume of the release medium, and V is the volume of each sample. Figure 8 It can be seen that the cumulative dissolution rate of BER API after 48 hours is about 27.18%, and the cumulative dissolution rate of BER-NCs prepared according to the preparation process of Example 1 is about 47.88%, which is about 1.76 times that of BER API, indicating that after BER is prepared into BER-NCs, the in vitro release rate is significantly improved and the dissolution rate is increased. The zero-order equation, the first-order equation and the Higuchi equation are respectively used to fit the cumulative release behavior of BER and BER-NCs. The in vitro release Qt curve fitting results are shown in Table 6. The correlation coefficient (R 2 ) It can be seen that the release of bergamot lactone and BER-NCs conforms to the first-order kinetic release equation, proving that the two are mainly released by diffusion control.

[0140] Table 6

[0141]

[0142] In summary, the poor solubility and low permeability of bergamot lactone are the main reasons that restrict its development. This project adopts a method combining thin film hydration and micro-media grinding to prepare bergamot lactone nanosuspension, aiming to solve the problem of poor solubility of bergamot lactone. The advantage is that nano-preparation can be effectively prepared. At the same time, the preparation only contains drugs and stabilizers, without introducing organic solvents and other impurities, and the drug loading is high, which is more conducive to industrial production. When investigating the preparation process of BER-NCs suspension in this study, it was found that the particle size of bergamot lactone nanocrystals prepared when Tween 80 was used as a stabilizer was smaller. The reason may be that Tween 80 can form a huge mechanical and thermodynamic barrier at the interface, reducing the surface tension between nanocrystals and medium solution. When optimizing the preparation process by Box-Behnken response surface method, the lack of fit term is not significant, the model fit is good, and the predictability is high. The actual particle size and PDI of the three batches of samples prepared in the verification test are not significantly different from the predicted values, and the relative deviation is small, indicating that the established preparation process is reasonable and reliable and can be used for later experiments. During the preparation of nanocrystals, the crystal form of the drug may change, thereby affecting the solubility and dissolution of the drug. In this study, DSC analysis, XRPD and FTIR methods were used to analyze the crystal form of BER API and BER-NCs to investigate the effect of the preparation process on the BER crystal form. In the DSC results, the melting points of the physical mixture and BER-NCs prepared by the corresponding process were slightly reduced, and the BER-NCs peak was wide and weak. It is reported that the decrease in the endothermic temperature is related to the decrease in particle size. In the XRPD results, the relative intensity of the BER-NCs diffraction peak decreased significantly compared with its API, which may be caused by the significant change in the drug particle size. In other words, the compactness of the arrangement of BER NCs molecules is reduced by the combined treatment of thin film hydration and micro-media grinding. It is speculated that the reason is the interaction of Tween 80 on the surface of BER nanocrystals, which may also make the diffraction peak intensity weaker than that of the API. In summary, this study successfully prepared and optimized the preparation process of BER-NCs. The quality of the prepared BER-NCs met the requirements and had good reproducibility, which laid a basic reference for further development of preparations and had good application prospects.

[0143] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing bergamot lactone nanocrystals, characterized in that: The following steps are involved: S1: weighing bergamot lactone and stabilizer in a mass ratio of 5:(1-4), then adding an appropriate amount of organic solvent to dissolve, and then removing the organic solvent by a reduced pressure rotary evaporation process to obtain a drug / stabilizer film; S2: hydrating the drug / stabilizer film obtained in S1 to obtain a drug solution; S3: After the hydration is complete, the drug solution in S2 is dispersed to obtain a drug suspension; S4: Add the drug suspension prepared in S3 into the medium grinding chamber for grinding to obtain BER nanocrystal suspension, i.e., BER-NCs.

2. The method for preparing bergamot lactone nanocrystals according to claim 1, characterized in that: In S1, polyoxyethylene sorbitan monooleate is used as the stabilizer.

3. A method for preparing bergamot lactone nanocrystals according to claim 2, characterized in that: In S2, the hydration process is as follows: add an appropriate amount of deionized water to the drug / stabilizer film obtained in S1 to prepare a drug solution, transfer it to a constant temperature magnetic stirrer, and hydrate it at room temperature for 5-6 hours.

4. The method for preparing bergamot lactone nanocrystals according to claim 3, characterized in that: In S2, the concentration of the drug solution was 5 mg / mL.

5. The method for preparing bergamot lactone nanocrystals according to claim 4, characterized in that: In S3, the dispersion process is as follows: in an ice-water bath environment, an ultrasonic cell pulverizer is used to disperse the drug solution in S2. The power of the ultrasonic cell pulverizer is 600 W, the dispersion time is 15 min, and it is turned on for 1 s and stopped for 1 s.

6. The method for preparing bergamot lactone nanocrystals according to claim 5, characterized in that: In S4, the grinding media is zirconia beads.

7. The method for preparing bergamot lactone nanocrystals according to claim 6, characterized in that: In S4, the volume ratio of grinding media to drug suspension was (1.8-2.2):

1.

8. The method for preparing bergamot lactone nanocrystals according to claim 7, characterized in that: In S4, the diameter of the zirconium oxide beads is 0.15-0.2 mm.

9. The method for preparing bergamot lactone nanocrystals according to claim 8, characterized in that: In S4, the grinding speed was 950-1100 rpm.

10. The method for preparing bergamot lactone nanocrystals according to claim 9, characterized in that: In S4, the grinding time is 12-16 h.